O efeito da bebida isotônica no desempenho de ciclistas recreativos - Pivetta, Franciele Marques (2018)
Movement strategies in cycling seem to be related to fatigue. The ingestion of isotonic beverages can be used aiming to improve exercise performance by delaying the time to fatigue onset. However, the effect of isotonic drink ingestion and the hydration status on fatigue establishment and cycling performance have been studied in athletes, but it is not fully explained for recreational cyclists. This study aimed to analyze the effects of previous ingestion of isotonic drink on the performance of recreational cyclists. Twenty-three male recreational cyclists were evaluated. Each cyclist performed two protocols in three days: incremental load (Day 1) and constant load (Day 2 and Day 3), with 48 – 72 hours interval between days. The incremental load protocol was performed with an initial load of 100 W, adding 30 W every minute until voluntary exhaustion. On the following days, a 60% of the maximum power was adopted at constant load tests. Cyclists consumed isotonic drink or placebo (double-blind design) and performed the constant load protocol until exhaustion. Physical performance (time to exhaustion) and hydration status were measured at the beginning and the end of the test. Every 3 min of the constant load protocol were measured: kinematic variables of the joints (hip, knee and ankle) and electromyographic representing the muscle activation pattern (rectus femoris, femoral biceps, anterior tibial and medial gastrocnemius) of the right lower limb, the subjective perception of exertion (Borg Scale) and the heart rate of each cyclist. In the first study (Chapter 3), an interaction between drink and time at the minimum angle and the mean angle of the ankle in the recovery phase was observed at the end of the test. The ankle joint presented an increase in plantar flexion with isotonic drink consumption compared to placebo consumption at the end of the test. For hip, knee and ankle joints there were no changes at the range of motion between drinks or over time. In the second study (Chapter 4), placebo intake had greater absolute dehydration, without differences in rate of dehydration. Only the anterior tibial and medial gastrocnemius muscles showed less overall muscle activation throughout the test. Tibialis anterior also presented a change in the frequency components, decreasing lower frequencies and increasing higher frequencies contributions over the time. In both studies, no differences were observed between beverages for the time until exhaustion, with increases in heart rate and subjective perception of effort (local and general) throughout the test. Our results indicate that previous isotonic drinking does not promote an increase in recreational cyclists performing physical performance during a constant load test until exhaustion.